Health Issues of Shipbreakers of Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Shipbreaking workers are vulnerable to long term health issues resulting from the poor environmental conditions existing in the shipbreaking yards of Bangladesh. The objective of this study was to identify the different respiratory health issues among longtime shipbreakers.  Materials and methods: This study involved observations and health testing of 25 workers engaged as shipbreakers for a minimum of 15 years. Informed written consent was obtained from each subject and health information was noted in a predesigned data sheet. Data was compiled and analyzed using SPSS 20.Results: The mean age of the shipbreakers were 49.28 years and the mean duration of work was 26.08 years. The  subjects experienced comorbidities such as hypertension  and peptic ulcer disease. Symptoms included cough, dyspnea on exertion, chest pain, weakness, and body swelling. Lab data revealed variable results of hemoglobin, Total Count (TC) Random Blood Sugar (RBS) serum creatinine, Alanine Transaminase (ALT) and Aspartate Transaminase (AST). X-ray findings and spirometry data showed mild to severe lung restriction with only 28% of the workers having normal spirometry results. Lung volumes revealed forced vital capacity (FVC), forced expiratory volume in one second (FEV1) and FEV1/FVC were 2.40±.69, 1.82±.58 and 77.56±16.27, respectively. High Resolution Chest Tomography (HRCT) showed apical fibrosis, bronchiectasis, Chronic Obstructive Pulmonary Disease (COPD) ground glass opacities, hyperinflated lungs with bullae and pleural thickening, mediastinal lymphadenopathy, old Tuberculosis (TB) changes, and pulmonary calcifications. Thirty-two percent of the HRCTs were normal.Conclusions: Shipbreaking workers participating in the study experienced significant occupational lung-related issues along with various comorbidities.JCMCTA 2023 ; 34 (1) : 106-110